Acquisition of t(11;14) in a patient with chronic lymphocytic leukemia carrying both t(14;19)(q32;q13.1) and +12. (31st May 2013) - Nishida, Yuhki; Takeuchi, Kengo; Tsuda, Kenji; Ugai, Tomotaka; Sugihara, Hiroki; Yamakura, Masayuki; Takeuchi, Masami; Matsue, Kosei
Abstract A rare recurrent chromosomal translocation, t(14;19)(q32;q13), has been identified in a variety of B‐cell malignancies, including chronic lymphocytic leukemia (CLL). We report a unique case of CLL in a patient carrying both trisomy 12 and t(14;19) (q32;q13.1), in whom t(11;14)(q13;q32) developed at relapse. The patient was a 77‐yr‐old woman, and her lymphoma cells at presentation showed CD5+, CD10−, CD19+, CD20+(dim), CD23+, CD38+, and CD11c+. At relapse, the patient's lymphoma cells showed positive staining for cyclin D1 in addition to CD5, CD20, and CD23. Lymphoma cells in specimens at both presentation and relapse were positive for lymphoid enhancer factor 1 (LEF1) and negative for sex‐determining region Y‐box 11 (SOX11). IGH‐BCL1 FISH became positive at relapse. Split FISH assay using BCL1, BCL3, IGH, and CCND1 probes on lymph node specimens obtained at presentation and at autopsy confirmed that the translocation of BCL3 was solely detected in the lymph node at presentation and detected BCL3 and CCND1 translocations in the specimen at autopsy. These observations indicated that IGH‐BCL3 and IGH‐CCND1 had occurred in the same clone after treatment of the disease. In line with immunohistochemical and cytogenetic studies, additional PCR analysis of the FR3‐JH region showed the same sequence derived from IGHV4‐34 in specimens obtained at disease onset and relapse.